Evaluation of vitamin D status, selenium and C-reactive protein level in psoriasis - Sumathi, S.; Babu, S. Vinod; Karthikeyan, K. (International Journal of Research in Dermatology, 2019)
Background: Psoriasis is an inflammatory skin disease associated with a variety of clinical conditions. Study aim to evaluate the association of vitamin D, selenium and C-reactive protein (CRP) levels in psoriasis. Methods: This hospital-based case-control study involved 50 psoriasis cases and 47 healthy individuals. Serum vitamin D, selenium and CRP levels were measured, and the general demographic values were also recorded. Results: Statistical analysis revealed that vitamin D levels are significantly lower in psoriasis (p<0.005). Among the demographic parameters, obesity was found more common among psoriasis cases than controls. Serum selenium and CRP levels were not significantly different between the two groups. Conclusions: Vitamin D deficiency is strongly associated with psoriasis. Vitamin D supplementation can be useful in psoriasis management and also in the reduction of obesity. Serum selenium and CRP levels aren’t significant markers to demonstrate psoriasis.